Pilgrimage Tourism And Its Importance In The Tourism Industry (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article Election is the main sign of civil society, the main sign of a democratic legal state. It is said that elections are an opportunity for citizens to actively participate in political processes in the main democratic system.